Strategi Pembelajaran Bahasa Indonesia untuk Meningkatkan Keterampilan Berbahasa - Rodia Tammardia Siregar; Rina Devianty (STIKes Ibnu Sina Ajibarang, 2024)
Learning cannot be separated from the existence of strategies in learning to improve language skills in everyday life. The learning process must be accompanied by attracting students' interest and tactics in improving language skills including listening skills, speaking skills, reading skills and writing skills. The aim of this research is that every educator must have a systematic Indonesian language learning strategy so that the learning process can improve language skills in students and can provide good results and achievements for generations of the nation and state. Because good language skills can make it easier for individuals to communicate and interact in everyday life.